Diet and gout – what is the role of purines?. Issue 2 (June 2016) - Lockyer, S.; Stanner, S.
Abstract: Anecdotally, consumption of 'rich' foods and drinks, such as cheese and port, has been associated with the development of gout, a painful condition linked to high serum uric acid which normally affects joints in the extremities, such as toes. Risk factors for gout include obesity, genetics and use of certain medications, and men appear to be more at risk. In addition, sufferers report that certain foods trigger gout flares, although there is a paucity of evidence from randomised controlled trials investigating the effect of specific foods on circulating uric acid. Observational studies have consistently identified a positive relationship between gout and some, but not all, foods higher in compounds known as purines, which have been demonstrated to increase serum uric acid in their purified form under controlled conditions. This evidence indicates that foods which should be avoided or consumed infrequently by gout sufferers are offal, seafood and alcohol, especially beer, whereas dairy foods seem to be protective. Current dietary guidelines for the prevention and management of gout share common features and largely reflect international healthy eating guidelines, but differences exist in terms of reference to particular foods or nutrients such as fructose, vitamin C and cherries. More randomised controlled trials are needed to fully ascertain the effects of dietary components on gout risk and to generate more consistent guidelines.